Investigation Of Ion Exchange Resins For Use In Treatment Of Semiconductor Processing Waste Streams - Jeffrey D. Winterton (The Minerals, Metals and Materials Society, 2005)
Keywords: Copper, ion exchange, sulfonic acid, bis-picolylamine, ion exchange modeling, ion exchange kinetics As part of an investigation into the feasibility of using ion exchange resins to recover copper from aqueous waste streams generated during the manufacturing of semiconductor devices, the uptake of copper onto two ion exchange resins was investigated. The resins studied were DOWEX G-26, a standard gel type sulfonic acid resin, and DOWEX M4195, a macroporous chelating resin with a bis-picolylamine functional group. The equilibrium and kinetic behavior of the uptake of copper were investigated over a range of copper concentrations with constant sulfate concentration and different levels of acidity. The homogeneous structure of the G-26 resin yields equilibrium relationships that fit the Langmuir equation, and equilibration times of less than 30 minutes. The uptake behavior of M4195 is complicated by the need to absorb co-ions to maintain electroneutrality, resulting in uptake profiles that change character with increasing copper concentrations, and extended equilibration times.